2021
DOI: 10.1155/2021/8320714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Number of Nozzles of Swirl Flow Generator Utilized in Flat Plate Solar Collector: An Entropic Analysis

Abstract: The numerical model of the pipes of a flat plate solar collector (FPSC) with several nozzles has been investigated in the present study. Indeed, the effect of the number of nozzles of the swirl generator on the entropic characteristics has been evaluated. The nozzles were applied for improving the performance of FPSC. For evaluating the proposed system based on the entropy concept, the effect of injection angle and mass flow rate has been considered. The selected injection angles were 30°, 45°, 60°, and 90°. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They observed that maximum efficiency of 60% was obtained in the flat-plate collector by improving the evaporation rate with the aid of six microcompartments in the collector basin. Cao et al [27] numerically investigated the entropic properties of flat-plate solar collector (FPSC) with the number of swirls generating nozzles. They predicted the overall system performance using N E , N S , Nu, and heat transfer improvement (HTI).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that maximum efficiency of 60% was obtained in the flat-plate collector by improving the evaporation rate with the aid of six microcompartments in the collector basin. Cao et al [27] numerically investigated the entropic properties of flat-plate solar collector (FPSC) with the number of swirls generating nozzles. They predicted the overall system performance using N E , N S , Nu, and heat transfer improvement (HTI).…”
Section: Introductionmentioning
confidence: 99%